Exploring the boundaries of refugee law : current protection challenges - Gauci, Jean-Pierre; Giuffré, Mariagiulia; Tsourdi, Evangelia (International refugee law series ;, 2015)
Protection challenges around the globe require innovative legal, policy and practical responses. Drawing primarily from a new generation of researchers in the field of refugee law, this volume explores the 'boundaries' of refugee law. On the one hand, it ascertains the scope of the legal provisions by highlighting new trends in State practice and analysing the jurisprudence of international human rights bodies, as well as national and international Courts. On the other hand, it marks the boundaries of refugee law as 'legal frontiers' whilst exploring new approaches and new frameworks that are necessary in order to address the emerging protection challenges.